AN ECONOMIC ANALYSIS OF THE IMPACT OF THE IRAQI DINAR EXCHANGE RATE ON THE IMPORTED QUANTITIES OF RICE DURING THE PERIOD 1990 - 2020 - Sanaa J. Mohamed,; O. H. Salman, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This research was aimed to analyze the impact of the Iraqi dinar exchange rates for the period 1990-2020 on the imported quantities of rice crop, and to measure the price elasticity of demand for this crop. The (ADRL) model was applied to measure the impact of these prices in addition to the (international price).After conducting the statistical tests (Dickie Fuller test) to examine the stability of the time series of the studied variables included in the model, which stabilized after taking the first difference for them, the results of the analysis showed that international prices had a weak effect on the imported quantities of rice crop, and that these quantities increased at an annual growth rate 6% more than the increase in the annual growth rate of foreign prices amounting to 2%, because the rice crop is one of the basic food crops in the Iraqi consumer list and that it is included in the items of the ration card distributed to individuals and therefore it is imported by the state to meet the need regardless of the rise in its prices. The private sector also imports high-quality brands regardless of prices. As for the equilibrium exchange rate, which is usually higher than the nominal exchange rate adopted by importers in obtaining foreign currency from unofficial markets, the higher the exchange rate, the lower the quantity imported, and the fixation of the nominal exchange rate for many years had a positive impact on the quantities imported by The government, so it is necessary to set an exchange rate for the Iraqi dinar that takes into account the purchasing power towards importing basic food commodities on which the community depends entirely for nutrition.